A Threshold-Blind Signature Scheme and Its Application in Blockchain-Based Systems - Victor Reyes-Macedo; Akinori Kawachi; Gina Gallegos-Garcia; Moises Salinas-Rosales (IEEE Access, 2024)
In blockchain-based systems usually there are two common concerns: one of them is privacy and other is key management. Besides privacy has been widely studied, nor key management has been done so deeply, moreover, the conjunction of both neither has be addressed. In this work we present a threshold blind signature scheme designed on the modified version of the Paillier cryptosystem presented by Yi et al. Our scheme guarantees four main characteristics of interest: Independence meaning that our scheme could be applied to any blockchain-based transaction system, allowing to adapt it to different application scenarios, i.e. electronic voting or founds administration; secure key storage which improves the key management security by recovering the whole signature instead of the private key and avoiding to have one single point of failure. In addition, we also provide anonymity as one of the best-evaluated features on online transactions. Finally, we achieve independence from mixers or trusted third parties, which most of the time are used to reach anonymity with inherent risks. All of these characteristics are achieved without increase computational and communication cost in comparison with related work.